MANAGEMENT OF INNOVATIVE DEVELOPMENT OF TOURISM ENTERPRISESUNDER THE CONDITIONS OF STRENGTHENING OF GLOBALIZATION PROCESSES - BILETSKA, IRYNA; ROMANCHUKEVYCH, MARIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article summarizes the features of world tourism development in the context of strengthening of globalization processes. It is established that the process of managing the innovative development of tourism enterprises should be structured and consistent. The stages of coordination of the management system of innovative development of tourism enterprises with modern tendencies of globalization and functioning of world tourism are determined. Priority measures have been systematized, which will ensure the effective functioning of tourism enterprises and minimize the risks of current activity in the context of strengthening of globalization. Differentiation of priority directions for coordinating the management of innovative development of tourism enterprises with the processes of globalization of world tourism depending on their specialization is carried out. It is concluded that the implementation of the proposed tools for coordinating the management of innovative development of tourism enterprises in the context of globalization creates the preconditions for improving the efficiency of their resource potential under increasing competition in the global tourism market.